Analyzing Social Services for Child Victims of Violence: A Case from Malang, Indonesia - Sukmana, Oman; Ibrahim, Fadli Erwan; Nugroho, Agung; Sulatsri; Sukmana, Erinda Dwimagistri; Wahyudi (NAJAHA, 2025)
The phenomenon of child maltreatment, including physical, sexual, social violence, emotional abuse, or neglect towards children in Indonesia, tends to increase. Child victims of maltreatment will experience various psychosocial problems, requiring assistance and social welfare services. This study aims to analyze the forms of social welfare service programs for child victims of maltreatment in Malang City. The research approach uses a qualitative method and the research subjects were purposively determined, specifically employees of the Office of Women's Empowerment and Child Protection in Malang City. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques followed the stages of qualitative data processing, which include Data Collection, Data Display, Data Condensation, and Conclusion and Verification. The results indicate that forms of violence against children include physical violence, psychological violence, sexual abuse, maltreatment, and neglect or abandonment. Meanwhile, the social welfare service programs for child victims of maltreatment include social assistance in the form of psychological support and consultation, social support (social aid) in the form of goods, and social protection in the form of social advocacy.